The G20 debate on Environmental Issues: is minilateralism the solution? - Oliveira, Vinicius Tavares de; Silveira, Mariana Balau (Monções: Revista de Relações Internacionais da UFGD, 2015)
Global range climate change institutions and conferences (e.g.: UNEP, COP etc.) have been part of international dynamics for decades. Many of them took place in international regimes that was specifically designed for environmental issues. G20 was created in 1999 with the goal to overcome the Asian crisis. In that moment little attention was given to environmental issues. This situation began to change in 2008 with the first G20 summit. In that occasion, only 2 paragraphs of the final declaration dealt with climate issues. In 2010, this number grew to 12.7. This shows a growing commitment of the forum to deal with climate issues. The purpose of this paper is to evaluate if and how G20 debate on climate change could help the world to achieve deeper environmental cooperation.